The Implementation of Akhlakul Karimah Values in the Learning Process at Al-Hikmah Private High School Medan During the Industrial Revolution 4.0 Era - Chandra, Bobby; Naimi, Nadlrah (Yayasan Rahmat Islamiyah, 2025)
This study aims to describe the implementation of Akhlakul Karimah values in the learning process at Al-Hikmah Private High School Medan during the Industrial Revolution 4.0 era. The research uses a qualitative descriptive method with observation, interviews, and documentation as data collection techniques. The results show that the teachers at Al-Hikmah Private High School integrate Akhlakul Karimah values through various learning activities, such as discipline, respect, honesty, and responsibility, which are aligned with Islamic teachings. In addition, the use of digital technology is directed to support character formation rather than merely cognitive achievement. The main challenges include students’ dependence on technology and the need for teacher innovation in integrating moral education with digital learning. The findings highlight that character education through Akhlakul Karimah remains essential in forming students’ Islamic personalities in the era of rapid technological advancement.